Paradigms, cities and epidemics - Chávez Vargas, Mariel Cynthia (2021)
This article takes a tour from the beginning of the 20th century on the main epidemics that shook Peru. However, the emphasis falls on contextual analysis through the influence of the development paradigms that accompanied these decades. The journey begins by observing how diseases accelerated reforms in public health and sanitation, moving to a stage where the conception of health is aligned with the developmental model characterized by state intervention, which also marks the beginning of the Latin American urban phenomenon. After its depletion, dismantling and under the belief in open and competitive markets as an optimal development mechanism, the inherited problems and inequalities of the previous period become more acute. When the COVID-19 pandemic arrives, like the predecessor epidemics, the series of accumulated deficiencies stand out, demanding once again, answers that touch on fundamental issues.